A Buddhist Modern Science: Measurement of Administrators - Sinthunok, Thitiwan; Munyapho, Jesada (Asia Pacific Journal of Religions and Cultures, 2020)
A state and country are the same meaning, by meaning that the land has the certain boundary, living people, administrators, sovereignty in self-administration but the word “country” emphasizes the structure of the geography. Whereas the word “state” focuses on the politics and administration and uses the power in administration, management of administration order of the state or management of system in applying the power to govern the state by depending on one kind of science, that is, “the political science” . When the orderly management of state and the administrators are created, how the management within the state will be, this item must depend on one kind of science, that is, the public administration. It can be seen that in the public policy, Buddhism teaches clearly, if ones who concern with designation of public policy bring the mentioned teachings to be used in designating the policy, it will cause the public policy to be good and efficiency and result in the people’s happiness and peace of society and cause the stability and progression of the nation that is the goal of the public administration.